Clostridium difficile Enterocolitis and Reactive Arthritis: A Case Report and Review of the Literature. (14th April 2016) - Cappella, Michela; Pugliese, Fabrizio; Zucchini, Andrea; Marchetti, Federico
Abstract : Reactive arthritis is a rare complication of Clostridium difficile enterocolitis, especially in children. We review the 6 pediatric cases published in the English and non-English literature and discuss their clinical presentation, outcome, treatment, and pathophysiology. We also report the seventh case of Clostridium difficile reactive arthritis in a 6-year-old boy who was treated with amoxicillin-clavulanate for 10 days because of an upper respiratory infection. After the antibiotic course, the child developed at the same time diarrhea with positive stool culture for Clostridium difficile and an asymmetric polyarthritis. Nonsteroidal anti-inflammatory drugs and metronidazole completely resolved the pain, joint swelling, and diarrhea. After twelve months of follow-up there has been no recurrence. This report confirms the self-limiting course of Clostridium difficile reactive arthritis. Clostridium difficile testing in children with gastrointestinal symptoms and acute onset of joint pain should be always considered.